High performance liquid chromatography mass spectrometric method for the simultaneous quantification of pravastatin and aspirin in human plasma: Pharmacokinetic application - Srinivasa Rao Polagani; Nageswara Rao Pilli; Venkateswarlu Gandu (Elsevier, 2012)
A rapid and sensitive liquid chromatographyâtandem mass spectrometric (LCâMS/MS) assay method has been developed and fully validated for the simultaneous quantification of pravastatin and aspirin in human plasma. Furosemide was used as an internal standard. Analytes and the internal standard were extracted from human plasma by liquidâliquid extraction technique using methyl tertiary butyl ether. The reconstituted samples were chromatographed on a Zorbax SB-C18 column by using a mixture of 5Â mM ammonium acetate buffer and acetonitrile (20:80, v/v) as the mobile phase at a flow rate of 0.8Â mL/min. The calibration curve obtained was linear (râ¥0.99) over the concentration range of 0.50â600.29Â ng/mL for pravastatin and 20.07â2012.00Â ng/mL for aspirin. Method validation was performed as per FDA guidelines and the results met the acceptance criteria. A run time of 2.0Â min for each sample made it possible to analyze more than 400 human plasma samples per day. The proposed method was found to be applicable to clinical studies. Keywords: Pravastatin, Aspirin, Human plasma, Liquidâliquid extraction, LCâMS/MS, Pharmacokinetics